Hubungan Antara Tayangan Iklan dalam Sinetron Anak Langit dengan Pengetahuan Siswa-Siswi SMKN 2 Karawang terhadap Produk Pop Mie Pedes Dower - Ana Fitriana P.; Atika Rosyada (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2018)
This study aims to determine the relationship between Ads Impressions in cinema Anak Langit with Knowledge of Vocational High School 2 Karawang Students towards Pop Mie Pedes Dower Product. This research uses Quantitative method. Respondents in this study were the students of Vocational High School 2 Karawang. Data collection techniques used in this study using questionnaires / questionnaires and literature study. The results of the research show that the relationship of ad impressions in cinema Anak Langit has a strong relationship with knowledge of Vocational High School 2 Karawangstudents towards Pop Mie Pedes Dower product with value (rs = 0,674). Knowledge of the product is influenced by ad impressions in soap operas that include thoughts about advertising messages, thoughts about the source of advertising, and thoughts about advertising. Keywords: Impressions, Product Knowledge, Advertising Messages, Advertising Source, Advertising